Anal Extrusion of Ventriculoperitoneal Shunt: A Case Report and Review of Literature - Farhad Bal'afif; Donny Wisnu Wardhana; Tommy Alfandy Nazwar; Novia Ayuning Nastiti (Fakultas Kedokteran Universitas Brawijaya, 2021)
Ventriculoperitoneal (VP) Shunt is a commonly performed surgical procedure and offers a good result in the treatment of hydrocephalus. In general, 25% of the complication rate of this surgical procedure is abdominal complications. Anal extrusion of a peritoneal catheter is a rare complication ranging from 0.1 to 0.7% of all shunt surgeries. This study presents a rare case of anal extrusion of ventriculoperitoneal shunt in a 1-year-old female child who was asymptomatic. The physical examination revealed swelling and redness along the shunt tract on the retro auricular region, soft abdomen, and no catheter was observed in the anal. This study found several contributing factors affecting the complications in the anal extrusion of a peritoneal catheter, that are thin bowel wall in children and sharp tip and stiff end of VP shunt. The shunt should be disconnected from the abdominal wall, and the lower end should be removed through the rectum by colonoscopy or sigmoidoscopy/proctoscopy or by applying gentle traction on the protruding tube. This study concludes that due to potentially life-threatening consequences and case rarity, thorough anamnesis, physical examination, and objective investigation are needed to determine the appropriate management for anal extrusion of ventriculoperitoneal shunt.Â